Effect on the clotting system of Peruvian fruit and vegetable juice - Zarzosa-Norabuena, Edwin (2015)
Objective: Verify the anticoagulant effect in vitro and in vivo of Peruvian fruit and vegetable juice and identify the coagulation pathway on which it acts. Material and Methods: Extracted juices of Ananascomosus (L.) Merr, Citrus limonunRisso, Carica papaya L., Allium sativum L., Allium cepa L. and Zingiber officinale L. Roscoe. An in vitro study with human plasma and in vivo administering juice orally to rats for 14 days. Anticoagulant activity was evaluated by measuring the prothrombin time (PT) and partial activated thromboplastin time (APTT), the Fibrinogen was also determined. Results: In vitro juices of Ananas and Zingiber prolonged PT, Carica prolonged APTT and Citrus, Allium sativum and cepa prolonged both tests. In vivo, juices of Allium cepa and Carica prolonged PT, citrus prolonged APTT, and Anannas both tests. The juices of Anannas, Citrus, Allium sativum and Zingiber decreased Fibrinogen. Conclusion: In vitro and in vivo Ananascomosus, Citrus limonun, Carica papaya and Allium cepa juices have anticoagulant effect. The juices of Allium sativum and Zingiber officinale, have this effect only in vitro.